Persistent organic pollutants exposure in newborn dried blood spots and infant weight status: A case-control study of low-income Hispanic mother-infant pairs - Gross, Rachel S. (Environ Pollut, 2020)
Persistent organic pollutants (POPs) are believed to alter metabolic homeostasis during fetal development, leading to childhood obesity. However, limited studies have explored how fetal chemical exposures relate to birth and infant weight outcomes in low-income Hispanic families at the highest risk of obesity. Therefore, we sought to determine associations between neonatal POPs exposure measured in newborn dried blood spots (DBS) and prenatal diet quality, birth weight, and overweight status at 18 months old. We conducted a case-control study nested within the Starting Early Program randomized controlled trial comparing POPs concentrations in infants with healthy weight (n=46) and overweight status (n=52) at age 18 months. Three categories of POPs, organochlorine pesticides (OCPs), polybrominated diphenyl ethers (PBDEs) and perfluoroalkyl substances (PFASs) were measured in archived newborn DBS. We assessed correlations between prenatal diet quality and neonatal POPs concentrations. Multivariable regression analyses examined associations between POPs (dichotomized at the mean) and birth weight z-score and weight status at 18 months, controlling for confounders. Seven of eight chemicals had detectable levels in greater than 94% of the sample. Higher protein, sodium and refined grain intake during pregnancy were correlated with lower POPs in newborn DBS. We found that high concentrations of perfluorooctanesulfonate (unstandardized coefficient [B]: −0.62, 95% confidence interval [CI]: −0.96 to −0.29) and perfluorohexanesulfate (B: −0.65, 95% CI: −0.99 to −0.31) were related to lower birth weight z-scores compared to those with low concentrations. We did not find associations between PBDEs, OCPs, and the other PFASs with birth weight z-scores, or between any POPs and weight status at 18 months. In conclusion, two PFASs were associated with lower birth weight, an important indicator of child health and growth, although direct associations with infant overweight status were not found. Whether neonatal POPs exposures contribute to economic and ethnic disparities in early obesity remains unclear.